Adjuvant strategies to improve vaccination of the elderly population. (August 2018) - Weinberger, Birgit
Highlights: Most current vaccines are less immunogenic and efficient in the older population. New adjuvants have improved vaccination success for several vaccines. Various classes of adjuvants are currently developed for use in the elderly. Research on immunosenescence and mode of action enables rational design of adjuvants. Abstract : Immunosenescence contributes to increased incidence and severity of many infections in old age and is responsible for impaired immunogenicity and efficacy of vaccines. Adjuvants are one strategy to enhance immunogenicity of vaccines. The oil-in-water emulsions MF59TM and AS03, as well as a virosomal vaccine have been licensed in seasonal or pandemic influenza vaccines and are/were used successfully in the elderly. AS01, a liposome-based adjuvant comprising two immunostimulants has recently been approved in a recombinant protein vaccine for older adults, which showed very high efficacy against herpes zoster in clinical trials. Several adjuvants for use in the older population are in clinical and preclinical development and will hopefully improve vaccines for this age group in the future.